2019
DOI: 10.20945/2359-3997000000148
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial metabolic effects of fructose and glucose in type 1 diabetes patients: a pilot randomized crossover clinical trial

Abstract: Objective:To test the influence of oral fructose and glucose dose-response solutions in blood glucose (BG), glucagon, triglycerides, uricaemia, and malondialdehyde in postprandial states in type 1 diabetes mellitus (T1DM) patients. Subjects and methods: The study had a simple-blind, randomized, two-way crossover design in which T1DM patients were selected to receive fructose and glucose solutions (75g of sugars dissolved in 200 mL of mineral-water) in two separate study days, with 2-7 weeks washout period. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
(44 reference statements)
0
4
0
4
Order By: Relevance
“…As for blood glucose control, it has been shown that fructose is a slow digestible carbohydrate that induces a lower postprandial blood glucose response than glucose in individuals with type 1 diabetes ( 12 , 13 ). This could explain the reduction in glucose variability in the first 3 months of the fruitarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…As for blood glucose control, it has been shown that fructose is a slow digestible carbohydrate that induces a lower postprandial blood glucose response than glucose in individuals with type 1 diabetes ( 12 , 13 ). This could explain the reduction in glucose variability in the first 3 months of the fruitarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fructose is converted to free fatty acids during de novo lipogenesis, but only to a small proportion of about 1-5 % [48]. Systematic reviews and meta-analyses, which included individuals with T1Dm, as well as a randomized controlled trial with T1Dm patients, show lower postprandial peaks for blood glucose, lower total cholesterol concentrations, no differences in other serum lipid parameters, but possibly increased uric acid concentrations and oxidative stress in an isocaloric comparison of fructose with other carbohydrates [49][50][51][52]. Due to the hepatic metabolization of fructose, its influence on hepatic insulin sensitivity is also widely discussed.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…Weiterhin wird Fruktose, jedoch nur zu einem geringen Anteil von etwa 1-5 %, in der de-novo-Lipogenese zu freien Fettsäuren konvertiert [48]. Systematische Reviews und Meta-Analysen, die neben anderen Personengruppen auch Individuen mit T1Dm inkludierten, sowie eine randomisierte kontrollierte Studie mit T1Dm Patienten zeigen bei einem isokalorischen Vergleich von Fruktose mit anderen Kohlenhydraten niedrigere postprandiale Peaks für Blutglukose, niedrigere Gesamtcholesterin-Konzentrationen, keine Unterschiede in anderen Serumlipidparametern, jedoch möglicherweise erhöhte Harnsäurekonzentrationen und oxidativen Stress [49][50][51][52]. Aufgrund des hepatischen Stoffwechsels der Fruktose wird auch ihr Einfluss auf die hepatische Insulinsensitivität vielfach diskutiert.…”
Section: Wissenschaf Tlicher Hintergrundunclassified